Adult participation in self-directed learning programs - Muhammad Madi Abdullah; Sebastian Francis Koren; Balakrishnan Muniapan; Balakrishnan Parasuraman; Balan Rathakrishnan (Canadian Center of Science and Education, 2008)
This paper attempts to explain the various concepts related to self-directed learning and also the various theories and models regarding adult participation and also non-participation in self-directed learning programs. Because of the extensive amount of previous literature and research findings dealing with self-directed learning, it is necessary to synthesize the relevant literature so that it can be useful as a basis for this and also for further research in this field. Conceptualization of self-directed learning will be reviewed in the wider and broader perspective. Also reviewed will be the development of self-directed learning, the definitions and characteristics of self-directed learning. Different conceptualization and factors contributing to adult participation in self-directed learning will be touched. In order to design an instrument and to develop a conceptual model, which adequately reflects those factors that have been reasonably determined to be relevant, it is felt that there was a need to identify those variables or factors, reported in earlier studies, which have been found to be significantly associated with adult participation in self-directed learning.